Cover Image. (11th October 2020) - Saknite, Inga; Zhao, Zijun; Patrinely, J. Randall; Byrne, Michael; Jagasia, Madan; Tkaczyk, Eric R.
Abstract : Cover Caption: The cover image © Inga Saknite, Vanderbilt Dermatology Translational Research Clinic is based on the Original Article INDIVIDUAL CELL MOTION IN HEALTHY HUMAN SKIN MICROVASCULATURE BY REFLECTANCE CONFOCAL VIDEO MICROSCOPY by Inga Saknite et al., https://doi.org/10.1111/micc.12621 .